THE EFFECT OF CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO AND SIZE ON FINANCIAL DISTRESS WITH PROFITABILITY AS A MODERATING VARIABLE IN PRIVATE BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN THE PERIOD 2018-2022 - Lala Merlita; Darmawati Muchtar; Ahmad Fauzul Hakim Hasibuan; Ghazali Syamni; Jummaini; Husaini (RADJA PUBLIKA, 2025)
This study aims to determine how Profitability (ROA) strengthens/weakens the influence of CAR, NPL, LDR, SIZE on financial distress in Private Banking Companies listed on the IDX. This type of research is quantitative descriptive. The population in this study are all private banking companies listed on the Indonesia Stock Exchange. Based on these provisions, the population of this study is 35 Private Banks. The companies selected as samples are 33 private companies. With the results CAR has a significant effect on financial distress in Private Banking Companies listed on the IDX. NPL does not have a significant effect on financial distress in Private Banking Companies listed on the IDX. LDR has a significant effect on financial distress in Private Banking Companies listed on the IDX. SIZE has a significant effect on financial distress in Private Banking Companies listed on the IDX. Profitability (ROA) has a significant effect on financial distress in Private Banking Companies listed on the IDX. Profitability (ROA) cannot moderate the effect of CAR on financial distress in Private Banking Companies listed on the IDX in this study, including in the Moderation Predictor (Predictor Moderation). Profitability (ROA) can moderate the effect of NPL on financial distress in Private Banking Companies listed on the IDX in this study, including in Quasi Moderation. Profitability (ROA) can moderate the effect of LDR on financial distress in Private Banking Companies listed on the IDX in this study, including in Quasi Moderation, Profitability (ROA) can moderate the effect of SIZE on financial distress in Private Banking Companies listed on the IDX in this study, including in Quasi Moderation.